If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(4x + 9) = 0 Reorder the terms: -3(9 + 4x) = 0 (9 * -3 + 4x * -3) = 0 (-27 + -12x) = 0 Solving -27 + -12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + -12x = 0 + 27 Combine like terms: -27 + 27 = 0 0 + -12x = 0 + 27 -12x = 0 + 27 Combine like terms: 0 + 27 = 27 -12x = 27 Divide each side by '-12'. x = -2.25 Simplifying x = -2.25
| -(3b-15)=(b+5) | | 5c-15= | | 2x-(-6x)-(4-2x)=3(x+2) | | 9a+37+8=0 | | 0.5t-0.2=-2.6-0.4(2t+7) | | -5+16=m-8 | | 12=x(x)-9x+23 | | 0.14y+0.05(y+3000)=1860 | | 13+295c-20=29 | | (3x+1)=76 | | 1x^2+12x+44=0 | | 5x+5-4x=14 | | 5(1-7b)=110 | | 11+6x=3(2x+4) | | 25-2x=15+8x | | 0.5t-0.2=2.6-0.4(2t+7) | | 7=x(x)-9x+23 | | x=0.5+2.25x | | 1.3x=2x+8 | | -(4-8b)=12 | | 4x-4=3x+4 | | 3w-4w-2=12 | | 7+29a-30=-9 | | -12m=-71 | | 4x^2-82x+210=0 | | 6x-4=2x+1 | | 2(x-6)=22 | | -2(x+1)=3x-1 | | y/8-5=-3 | | 6-7x=5x-9x-15 | | -4c-6c=-110 | | 9x^2-15=0 |